2019
DOI: 10.1124/jpet.119.261040
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Small Molecule Inhibits Tumor Growth and Synergizes Effects of Enzalutamide on Prostate Cancer

Abstract: Prostate cancer (PCa) is the second leading cause of cancerrelated death for men in the United States. Approximately 35% of PCa recurs and is often transformed to castration-resistant prostate cancer (CRPCa), the most deadly and aggressive form of PCa. However, the CRPCa standard-of-care treatment (enzalutamide with abiraterone) usually has limited efficacy. Herein, we report a novel molecule (PAWI-2) that inhibits cellular proliferation of androgen-sensitive and androgen-insensitive cells (LNCaP and PC-3, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…This is an important finding, considering the high mortality rates of prostate cancer due to metastasis development [44]. Regarding the treatment outcome of the single agents, our data confirmed that hydralazine downregulates cell invasion [45], whereas conflicting results were reported regarding enzalutamide, which has been described both as a suppressor [46], as well as a promoter of invasion [47].…”
Section: Discussionsupporting
confidence: 71%
“…This is an important finding, considering the high mortality rates of prostate cancer due to metastasis development [44]. Regarding the treatment outcome of the single agents, our data confirmed that hydralazine downregulates cell invasion [45], whereas conflicting results were reported regarding enzalutamide, which has been described both as a suppressor [46], as well as a promoter of invasion [47].…”
Section: Discussionsupporting
confidence: 71%
“…In vitro clonogenic assays simulate the seeding and proliferation of tumor initiating cells, i.e., cancer stem cells [74]. A number of previous studies have already been carried out in tumor xenografts in vivo using either clinically approved ENZ [75][76][77][78][79] or CDDO-Me [26,37,40,41,44] alone; and therefore, studies using the combination of CDDO-Me and ENZ in tumor-bearing mice, would be the next feasible direction of our current findings. Taken together, our in vitro finding suggests a possible benefit of using safe concentrations of CDDO-Me alone to suppress the growth of micro-metastatic foci, and as an adjunct therapy to enhance the efficacy of antiandrogens.…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that novel mitochondria-targeted therapeutic agents, like Pentamidine, Atpenin A5, and Urupocidin c could efficiently suppress PCa progression [ 51 53 ]. Moreover, PAWI-2 can activate mitochondrial-controlled p53-dependent apoptotic signaling and possesses promising therapeutic potency in low-dose combination therapy with enzalutamide [ 54 , 55 ]. In this study, we identified the PPFIA4-MTHFD2 axis as an important pathway to activate mitochondria metabolism and blocking this pathway by a specific inhibitor DS18561882 towards MTHFD2 could efficiently delay CRPC progression.…”
Section: Discussionmentioning
confidence: 99%